2019
DOI: 10.1017/s0022215119000197
|View full text |Cite
|
Sign up to set email alerts
|

Subjective morbidity following radial free flap reconstruction in head and neck tumour patients

Abstract: ObjectiveEvaluation of post-operative donor site disability remains unaddressed in radial forearm free flap cases. This study aimed to assess donor site dysfunction following radial forearm free flap harvest using validated general, disease-specific and site-specific disability questionnaires.MethodsIn this retrospective case series of 24 patients at a tertiary academic medical centre, patients were assessed using the Short Form 36 Health Survey, Short Musculoskeletal Function Assessment questionnaire, and Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Overall, mean DASH scores were low with "minimal to mild disability" scores appreciated across all free flap donor sites evaluated. The RFFF was evaluated in 203 patients across five studies [17][18][19][20][21] with an average postoperative time to DASH administration of 21 months (range 6-44). The pooled mean DASH score was 12.14 (95% CI: 7.40-16.88).…”
Section: Dash Scoresmentioning
confidence: 99%
“…Overall, mean DASH scores were low with "minimal to mild disability" scores appreciated across all free flap donor sites evaluated. The RFFF was evaluated in 203 patients across five studies [17][18][19][20][21] with an average postoperative time to DASH administration of 21 months (range 6-44). The pooled mean DASH score was 12.14 (95% CI: 7.40-16.88).…”
Section: Dash Scoresmentioning
confidence: 99%
“…разработали опросник для оценки нарушений функции предплечья и кисти в отдаленном периоде после забора лучевого лоскута. При использовании данного опросника авторы выявили долгосрочное нарушение функциональной активности руки, на которой расположена донорская зона [34].…”
Section: преимущества лучевого лоскутаunclassified
“…7 Moreover, donor site morbidity, potential flap failure, and other risks pertinent to the flap of choice must be considered. 8 Treatment of head and neck cancer utilizes significant healthcare resources. There have been multiple studies analyzing the cost implications of preoperative, perioperative, and postoperative care of patients undergoing MFTTone single-institutional study reported mean hospital charges for a free flap totaled $32,501 9 ; Overall costs rose to $47,708 when adjusted for inflation.…”
Section: Introductionmentioning
confidence: 99%
“…These complications are often associated with longer duration of mechanical ventilation, greater fluid shifts, and hemodynamic perturbations 7 . Moreover, donor site morbidity, potential flap failure, and other risks pertinent to the flap of choice must be considered 8 …”
Section: Introductionmentioning
confidence: 99%